Attitudes towards Thai English: Indonesian Pre-service Teachers Lenses During Teaching Practicum in Thailand - Firda Fauziyah; Arini Nurul Hidayati; Fuad Abdullah (STAI Hubbulwathan Duri, 2021)
Over the last few decades, World Englishes have shifted the paradigm of how both native and non-native speakers view English as a lingua franca. This paradigmatic shift has attracted scholars to conduct a plethora of investigations on the roles of English as an international language. However, scrutinizing the pre-service teachers’ attitudes towards Thai English amid their teaching practicum in Thailand remains under-explored, notably viewed from Indonesian perspectives. This study investigated Indonesian pre-service teachers’ attitudes towards Thai English within their teaching practicum in Thailand to fill this gap. Four Indonesian pre-service teachers performing teaching practicum at diverse Thai schools were recruited as the participants. The data were garnered through semi-structured interviews and analyzed with qualitative data analysis framework. The findings revealed that Thai English was less intelligible. Besides, they contended that Thai English enables them to experience emotional shifts. Eventually, Thai English has adapted from the English and Thai language. With these in mind, understanding and employing Thai English practically offers the Indonesian pre-service teachers another variety of English to communicate in the classroom.